Agricultural mechatronic research at Universiti Putra Malaysia - Wan Ismail, Wan Ishak (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The application of computer, mechatronics and machines for agricultural production has been one of the outstanding developments in Malaysian agriculture. This paper and presentation will describe on the recent research at Universiti Putra Malaysia (UPM) on the uses of camera vision system towards machines and equipments for the agricultural operations. Color vision is the most important indicator for the farmer to determine fresh fruit bunches (FFB) oil palm fruit maturity in manual harvesting process. The variations of the daylight caused changing the light intensity thus becomes the main issue that effect on automatic recognition process. In this study, the relationships of oil extraction rate (OER), fruit ripeness and fruit colour were determined. The objective of this project is to develop the software to enable the planters to determine the time of harvesting the matured fruits. The software was then downloaded to the handphone as a portable camera and portable computer for real-time determination of fruit maturity. Research on ‘Camera Vision to Determine the Oil Palm Yield’ describes on the use of Hemispherical Photography Camera to determine the Leaf Area Index (LAI) as the main factor in growth modeling of the crops. Canopy structure is an important variable for any physiology experiment as well as for studies related to radiation, photosynthesis, energy exchange, gas exchanges, nutrition analysis, fertilizer treatment, pest management and soil fertility analysis. Leaf area index is a main component of canopy structure. Based on the measurements of the geometry of sky visibility and sky obstruction, hemispherical photographs can be used to calculate solar radiation regimes and plant canopy characteristics such as Leaf Area Index (LAI). The equation of LAI was used to predict yield of crop. The research on ‘On-line automated weedicide sprayer system’ describes on how to locate in the real time environment the existence and intensity of weeds and to spray the weedicides automatically and precisely. The sprayer nozzle will turn ‘on’ or ‘off’ depending on the percentage or intensity of green color pixel value of weeds. The sprayer valve will open the nozzle/s when the camera detected the presence of weeds. The above concept can be applied to other agricultural operations such as grading of agricultural products in terms of color.